Defining democratic inclusion from the perspective of democracy and citizenship theory. Issue 8 (17th November 2022) - Zilla, Claudia
ABSTRACT: In political science, we deal with a series of ideas, which are primarily political ideals. In comparative politics, we need concepts that are able to "travel" across countries and regions and capable of being measured. Inclusion is an equivocal notion in which both aspects converge: On the one hand, inclusion is used as a code for normative claims regarding, for example, participation, equality, social justice and recognition. On the other hand, it can be applied as an analytical tool for assessing a quality of political regimes. How can inclusion be defined in order to maintain its value orientation and serve at the same time as an empirical concept for systematic-qualitative comparative research? Combining the perspectives of democracy and citizenship theory—two strands that run parallel to each other without much interaction—I define and operationalize inclusion as a property of democratic political systems. Starting from a normative conception of democracy and citizenship that leads to a procedural definition, I conceive of democratic inclusion as civic and political inclusion and lay out dimensions for comparatively assessing political regimes from the perspective of inclusionexclusion.